Empowerment of joint business groups for the family hope program (KUBE PKH) in Madang Suku III District, East OKU Regency South Sumatera Province - Imam Mahdi; Alfitri Alfitri; Ridha Taqwa (Enrichment : Journal of Management, 2023)
This study examines the empowerment efforts of Joint Business Groups (KUBE PKH) under the Family Hope Program in Madang Suku III Sub-District, East OKU Regency, South Sumatra Province. The Family Hope Program, or Program Keluarga Harapan (PKH), aims to alleviate poverty and improve the well-being of underprivileged families by providing financial assistance and promoting community-based business initiatives. The research assesses the effectiveness and impact of KUBE PKH in enhancing the socio-economic conditions of the target beneficiaries. Utilizing a mixed-method approach, data is collected through surveys, interviews, and field observations to gain comprehensive insights into the challenges and successes faced by the participating groups. The findings are expected to contribute valuable information to policy makers and stakeholders in refining and strengthening the KUBE PKH program as a means to empower marginalized communities and foster sustainable development in the region.